Analysis Of Determinants Of Employee Performance On Employees Of PT. Telkom Indonesia Witel Medan - Wahyudi Maherza (Yayasan Multidimensi Kreatif, 2025)
The purpose of this study is to evaluate various aspects of the performance of employees of PT. Telkom Witel Medan, such as communication, compensation, competence, and job satisfaction. The population is all employees of PT. Telkom Witel Medan. For this study, the sample selection consisted of 80 people. The data analysis techniques used are measurement model (outer model) and inner model consisting of convergent validity, dicriminant validity, model coloniality test, composite reliability, path coefficient, and R-Square which is processed using SEM – PLS (Structural Equation Modeling – Partial Least Square). Based on the outer model and inner model tests , no offensive variables were found. The results of this study show that: The following factors affect employee performance: communication affects employee performance, salary does not affect employee performance, competence does not affect employee performance, communication affects job satisfaction, salary affects job satisfaction, competency affects job satisfaction, job satisfaction affects employee performance, communication affects employee performance mediated by job satisfaction, salary affects employee performance mediated by job satisfaction.